2022
DOI: 10.1002/elan.202200003
|View full text |Cite
|
Sign up to set email alerts
|

Modified Separator with Nitrogen‐doped High‐graphitized Carbon for Lithium‐sulfur Batteries

Abstract: Suppressing the shuttling of dissolved lithium polysulfides (LiPSs) is an indispensable strategy to extend the cycling life of lithium-sulfur (LiÀ S) batteries. One strategy is absorbing the LiPSs by modifying separator of LiÀ S batteries. Herein, we show a novel nitrogen-doped graphitized carbon (NGC) derived from coconut shell, which was annealed by flash Joule heating at ultrahigh temperature within seconds. The NGC was coated on the polypropylene (PP) separator to prepare the modified PP separator, which e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…The surface of the TPP@PVDF/SiO 2 /GO separator before and after combustion was analyzed by Raman spectroscopy, as shown in Figure c. The Raman peaks at 1252 cm –1 (D) and 1500 cm –1 (G) indicated that amorphous and graphitized carbon coexisted in the surface . The intensity ratio of the D side to the G side ( I G / I D ) indicated the degree of graphitization ( S ) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The surface of the TPP@PVDF/SiO 2 /GO separator before and after combustion was analyzed by Raman spectroscopy, as shown in Figure c. The Raman peaks at 1252 cm –1 (D) and 1500 cm –1 (G) indicated that amorphous and graphitized carbon coexisted in the surface . The intensity ratio of the D side to the G side ( I G / I D ) indicated the degree of graphitization ( S ) .…”
Section: Resultsmentioning
confidence: 99%
“…The Raman peaks at 1252 cm −1 (D) and 1500 cm −1 (G) indicated that amorphous and graphitized carbon coexisted in the surface. 58 The intensity ratio of the D side to the G side (I G /I D ) indicated the degree of graphitization (S). 10 The S values of the composite membrane before and after combustion were 0.926 and 1.248, respectively.…”
Section: Flame-retardant Property and Thermal Stabilitymentioning
confidence: 99%
“…Integration of defect-rich carbon and commercial separator is an efficacious and practicable strategy. Wei et al 244 and lower decomposition energy barrier of Li2S, thus giving combed separator higher catalytic activity and faster conversion (Fig. 10c-10f).…”
Section: Materials Advances Accepted Manuscriptmentioning
confidence: 93%
“…Integration of defect-rich carbon and a commercial separator is an efficacious and practicable strategy. Wei et al 238…”
Section: Carbon-based Multifunctional Separatorsmentioning
confidence: 99%
See 1 more Smart Citation